2015
DOI: 10.1007/s11144-015-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide based solid acid as an efficient and reusable nano-catalyst for the green synthesis of diindolyl-oxindole derivatives in aqueous media

Abstract: Graphene oxide nanosheets were synthesized from natural graphite powder. The prepared catalyst was characterized by transmission electron microscopy, Fourier transform infrared spectroscopy, powder X-ray diffraction, thermogravimetric analysis and ultraviolet-visible spectroscopy. This heterogeneous catalyst was used for the Friedel-Crafts 3-indolylation reaction of isatin with indole derivatives in water as a green media in good to excellent yields. This method has advantages including the use of water as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A plausible mechanism for the GO-catalysed reaction of 3-diazo oxindole 1a and indole 2a is presented in Scheme 7. 30 First, GO facilitates protonation of the diazo compound. This protonation gives rise to the formation of the 2-oxoindoline-3-diazonium ion A , which possesses a highly electrophilic centre.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A plausible mechanism for the GO-catalysed reaction of 3-diazo oxindole 1a and indole 2a is presented in Scheme 7. 30 First, GO facilitates protonation of the diazo compound. This protonation gives rise to the formation of the 2-oxoindoline-3-diazonium ion A , which possesses a highly electrophilic centre.…”
Section: Resultsmentioning
confidence: 99%
“…29 Nasseri and co-workers synthesized diindolyl-oxindole using GO as an efficient and reusable heterogenous catalyst. 30 Recently, Zbořil et al reported the transformation of wastes into high-added-value chemicals using GO as an organocatalyst. 31 With our interest towards the development of environmentally friendly synthetic methodologies, herein we revealed a highly green and efficient synthesis of 3,3′,3″-trisindoles using GO as a heterogeneous catalyst in DMSO/water medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene oxide catalyzed the reaction between indoles and isatins in water media under ambient temperature to give trisindolines 3, 5, 15, 18, 21–25, 27, 31, 84–88, 99 and 100 in 65–98% yields within 1.5–5 h. 64 The best yields were obtained when the indoles were substituted with EDG on C-2 and/or isatins were substituted with EWG on C-5. EWG on C-5 of the indole decreased the yield and/or prolonged the reaction time.…”
Section: Synthesis Of Trisindolinesmentioning
confidence: 99%